O11.1. ASSOCIATION BETWEEN GLUTAMATE AND ACCELERATED BRAIN-AGEING IN TREATMENT-RESISTANT SCHIZOPHRENIA. (9th April 2019) - Mouchlianitis, Elias; Cole, James; Vanes, Lucy; Shergill, Sukhi
Abstract: Background: Previous studies have shown that glutamatergic dysfunction appears to be a stable neurobiological characteristic of antipsychotic treatment-resistance. At the same time, treatment-resistant patients show more pronounced neurostructural deficits when compared to treatment-responsive patients. However, this association between glutamate and neurostructural integrity has not been investigate before in patients with treatment-resistant schizophrenia. Methods: 42 participants with a diagnosis of schizophrenia and 20 healthy controls matched for age, sex, and socioeconomic background consented to participate in this study. We acquired T1-weighted magnetization prepared rapid acquisition gradient echo sequence and proton magnetic resonance spectroscopy at 3 Tesla from bilateral anterior cingulate cortex. The patient group was classified into 21 antipsychotic treatment-resistant patients and 21 antipsychotic treatment-responsive patients. To calculate brain-age we used a novel method termed brain-predicted age difference (brain-PAD; Cole et al., 2016). This method uses a machine-learning algorithm to calculate brain-age calculated from structural images. The model was trained on structural images from a large healthy reference sample (N=2001), which were used to predict chronological age in a Gaussian Process regression. The model estimates were used to predict brain-PAD in the participants of our study independently, using their T1 structural scans. Brain-PAD was calculated as brain-predicted age minus chronological age. Brain-PAD scores above zero indicate accelerated brain ageing. Using the T1-weighted MRI scans we also calculated cortical thickness using the standard recon-all pipeline available in Freesurfer 6.0 software. Cortical thickness was calculated over 34 regions of interest in each hemisphere based on the standard Desikan-Killiany atlas. 1H-MRS data were analyzed using a standard basis function within LC-Model. Our primary measure was glutamate to creatine ratio (Glu/Cre). Results: The main finding is that there was a significant positive correlation between anterior cingulate cortex Glu/Cre and brain-PAD only for the treatment-resistant patients, R=0.52, P=0.014, meaning that within this group higher Glu/Cre values were associated with accelerated brain ageing. There was no significant correlation for the treatment-responsive group, R=-0.23, P=0.33 or the healthy participants, R=0.09, P=0.78. Fisher's r-to-z transformations to test pair-wise group differences showed that Glu/Cr and brain-PAD correlation was significantly stronger in treatment-resistant patients when compared to treatment-responsive, Z=2.36, P=0.018 reflecting a large effect size of 0.81. The difference between treatment-resistant and healthy participants was at trend-level, Z=1.36, P=0.08, with a medium effect size of 0.49. There was no difference between treatment-responsive and healthy participants, Z=-0.92, P=0.36. A regression model including cortical thickness showed that for treatment-resistant patients, increase in strength of the relationship between Glu/Cre and brain-PAD was associated with cortical thickness reductions in right medial temporal lobe, bilateral inferior parietal lobe, right superior parietal lobe and precuneus. Discussion: We show for the first time that glutamate levels were associated with accelerated brain ageing in treatment-resistant patients. This is consistent with accounts of glutamate-mediated excitotocity. Our data suggest that glutamatergic dysfunction in patients with poor antipsychotic response can particularly affect neurostructural integrity in cortical regions associated with the pathoetiology of the disorder.